Climate vulnerability of agroecological and conventional smallholders in Mvomero district, Tanzania: using mixed-methods to uncover local experiences and motivations of farming for the future - Johansson, Emma; Martin, Respikius; Mapunda, Kenneth (Frontiers in Sustainable Food Systems, 2024)
Changing rainfall patterns make farmers increasingly vulnerable to crop failure, income loss and food insecurity. Agroecology is proposed to reduce climate vulnerabilities of farmers, as such practices and social movement aim to create more resilient farm and food systems. It is however fairly unknown if, and to what extent, agroecological farmers are better able to cope with climate induced exposures as compared to conventional smallholders. We conducted 194 surveys with agroecological and conventional smallholders to explore the three components of climate vulnerability: exposure, sensitivity and adaptive capacity. We combined this with field observations and interviews, and an analysis of long-term rainfall data. We also followed up the initial survey analysis with additional focus group discussions. Just as climate change occurs incrementally over time, we highlight modest, yet important differences between conventional and agroecological farmers. We find that agroecological farmers are less vulnerable to short-term dry spells, due to a combination of farming practices that improve soil water retention, like mulching and the use of cover crops. However, the use of botanicals might induce new vulnerabilities, as their processing requires additional labor, and sometimes expenditures, and may not protect the crops from pests and diseases. We also find limitations to agroecology in terms of scale, as most farmers are unable to use botanicals on all their farmland. Yet, agroecological farmers process and apply botanicals for health benefits both in production and consumption of foods, and they can occasionally sell their organic farm products for a higher price than conventional famers. With this study, we emphasize that farmers’ reasons to practice agroecology is not just to boost productivity and become more climate resilient, but rather for improving the long-term health of producers, consumers, soils and the environment.